Plasticity of executive functions after traumatic brain injury in adolescents - Vander Linden, Catharine; Verhelst, Helena; Deblaere, Karel; Caeyenberghs, Karen; Vingerhoets, Guy (Belgian Journal of Paediatrics, 2023)
Children with a moderate to severe traumatic brain injury do recover quite well when it comes to talking and walking. They frequently may appear to make a full physical recovery and at the end of the rehabilitation period do often perform within the average range in various physical and standardized neuropsychological assessments. However, regardless of their performance on standardized tests, everyday functioning at home or in school remains generally poor. ‘The hidden disability’ such as difficulties in executive function and sometimes an ‘unusual’ behavior jeopardizes future socio-economic integration and can be deeply distressing for parents and siblings. Rehabilitation is essential to foster reorganization and further maturation of the child’s brain, not only immediately post-injury but alongside the ongoing acquisition of higher cognitive skills. A computerized training program can provide a therapeutic manipulation of functional and structural neuroplasticity in the traumatized developing brain to enhance recovery and continuing maturation of executive function.